2017
DOI: 10.1080/09688080.2017.1378532
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of displaced Syrian women and service providers on fertility behaviour and available services in West Bekaa, Lebanon

Abstract: Prior to the conflict, Syria had relatively high fertility rates. In 2010, it had the sixth highest total fertility rate in the Arab World, but it witnessed a fertility decline before the conflict in 2011. Displacement during conflict influences fertility behaviour, and meeting the contraceptive needs of displaced populations is complex. This study explored the perspectives of women and service providers about fertility behaviour of and service provision to Syrian refugee women in Bekaa, Lebanon. We used quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 19 publications
(20 reference statements)
2
51
1
11
Order By: Relevance
“…These safety concerns have, in part, led to an increased rate of child marriage and decreased age at which many Syrian girls are married in Lebanon [7]. Reports indicate that some Syrian families feel threatened by the more 'liberal' Lebanese values, economic insecurity, lack of access to education for girls, and fear of physical harm [5,8,9], perhaps contributing to decisions to marry their daughters earlier. In 2017, approximately 35% of Syrian refugee girls in Lebanon were reportedly married before the age of 18 compared to 13% of girls marrying in Syria before the age of 18 in 2006 [10].…”
Section: Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…These safety concerns have, in part, led to an increased rate of child marriage and decreased age at which many Syrian girls are married in Lebanon [7]. Reports indicate that some Syrian families feel threatened by the more 'liberal' Lebanese values, economic insecurity, lack of access to education for girls, and fear of physical harm [5,8,9], perhaps contributing to decisions to marry their daughters earlier. In 2017, approximately 35% of Syrian refugee girls in Lebanon were reportedly married before the age of 18 compared to 13% of girls marrying in Syria before the age of 18 in 2006 [10].…”
Section: Contextmentioning
confidence: 99%
“…Fertility patterns are a complex issue driven by a range of interconnected factors [8,21]. Earlier qualitative research with Syrian women in Lebanon identified a number of reasons for wanting children, including believing that it was god's will, believing that having more children would increase access to aid, wanting to replace children lost in the conflict, concern about the cost of contraception, and desperation to have a son [8].…”
Section: Sexual and Reproductive Health Among Displaced Syrian Women mentioning
confidence: 99%
See 3 more Smart Citations